Open-path cavity ring-down spectroscopy for the detection of hydrogen chloride gas and particles in a cleanroom environment - Khan, Muhammad Bilal, author; Yalin, Azer P., advisor; L'Orange, Christian, advisor; Yost, Dylan, committee member (Colorado State University. Libraries, 2024)
Semiconductor chips are the driving force behind the electronics industry, and modern technology depends on these vital chips to function. The size of these semiconductors has been steadily decreasing in accordance with Moore's law. The increasingly smaller feature sizes require very pristine cleanroom manufacturing environments to ensure minimal contamination from unwanted gases and particles. Two of the main contaminants to monitor in a cleanroom are gaseous hydrogen chloride (HCl) and airborne particles. HCl is a corrosive gas that affects the lifespan of equipment, infrastructure, and ventilation systems while also negatively impacting human health. Likewise, the presence of airborne particles is problematic since it can result in yield loss due to blockage of the inscription of miniature circuits on the wafers. Manufacturing must occur in spaces between ISO 3 to 8 (International Organization for Standardization) requiring precise monitoring of particles. The overarching goal of the present research is to develop new cleanroom monitoring methods for HCl and particles based on novel laser instrumentation. An acrylic chamber with controlled inlet and outlet flow was constructed and utilized to simulate cleanroom conditions. This chamber allowed for controlled air flows mixed with HCl gas in the range of ~0-100 parts-per-million (ppm) or particles at ISO levels of ~≤3-9. Detection of both HCl and particles uses a single continuous-wave 1742 nm near-infrared laser as a light source for open path cavity ring-down spectroscopy (CRDS). The compact laser system consists of a 60 cm cavity. High sensitivity detection of HCl is achieved by probing the 2-0 vibrational band of HCl (R(3) line). The CRDS system can accurately detect HCl with an Allan deviation of 0.15 ppb over a 10-minute duration. Several approaches for particle detection based on analyzing the small fluctuations in ring-down times caused by Mie scattering are examined. The most sensitive particle detection uses statistical analysis of ring-down times based on the 3rd and 4th standard moments allowing the detection of particles (diameter > 1 μm) at low concentrations down to ISO of approximately 5. The results provide a promising foundation for the development of open-path CRDS laser instrumentation for cleanroom monitoring.
Keywords: cavity ring down spectroscopy; CRDS; particles; cleanroom; AMC; HCL